PENCEGAHAN DBD PADA MASYARAKAT DAYAK DIWILAYAH KELURAHAN PAMPANG SAMARINDA KALIMANTAN TIMUR - Badar Badar; Lukman Nulhakim; Rasmun Rasmun (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2021)
Abstract Introduction: Various cultures in East Kalimantan, one of which is the Dayak Kenyah ethnic culture inhabiting the Pampang Cultural Village. Purpose: This study analyzes the prevention of DHF in Pampang Samarinda Utara Village in 2020. Methods: Using a qualitative design with an ethnographic approach, sources of information from 5 main informants, 1 key informant, 1 supporting informant, Milles and Huberman models are used in data analysis with the Opencode 4.03 application. Results: Informants' knowledge about dengue fever is a new disease. The attitude of the informants still holds the culture in their daily life. Informants still depends on nature. Informants' DHF prevention measures, performing dance ceremonies (Mentiang), are still largely dependent on natural products which are used as a source of medicines (Taban). Conclusion: In general, the informants referred to DHF as